1991
DOI: 10.1159/000261375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Acidic Calcium Phosphate Solution and the Intraoral Fluoride-Releasing Device on Dental Caries and Fluoride Uptake in Rats

Abstract: This investigation comprised two studies evaluating the effects of an acidic calcium phosphate solution (CPS) on fluoride uptake in the enamel, glycolysis of dental plaque, the incidence of dental caries and urinary fluoride concentrations of rats wearing an intraoral fluoride-releasing device (IFRD). In the first study, CPS-fluoride treatment preceded the cariogenic challenge. In the second study, the cariogenic challenge preceded the treatments. In the first study, CPS treatments increased the ability of ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In addition, Mirth reported a 40% reduction in occlusal fissure caries compared with the control group, a site thought not to be normally protected by fluoride. Shern et al [1991] found that the copolymer devices significantly restricted the development of carious enamel on the sulcal-morsal surfaces in rats. The only human caries study to be reported is by using the fluoride glass devices.…”
Section: Caries Studiesmentioning
confidence: 95%
“…In addition, Mirth reported a 40% reduction in occlusal fissure caries compared with the control group, a site thought not to be normally protected by fluoride. Shern et al [1991] found that the copolymer devices significantly restricted the development of carious enamel on the sulcal-morsal surfaces in rats. The only human caries study to be reported is by using the fluoride glass devices.…”
Section: Caries Studiesmentioning
confidence: 95%
“…The most interesting finding, however, was that the occlusal surfaces were also protected in that study, since 40% fewer occlusal caries lesions were found in the test group. Another study using a similar protocol also demonstrated that the copolymer device significantly restricted the development of enamel caries on the sulcal-morsal surfaces in rats 45 .…”
Section: Effect On Caries Prevalence Reductionmentioning
confidence: 85%